Improving Narrative Writing Skills of Secondary Students with Disabilities Using Strategy Instruction. Issue 4 (2nd October 2017) - Foxworth, Lauren L.; Mason, Linda H.; Hughes, Charles A.
ABSTRACT: Writing standards and objectives outline complex skills for narrative essay writing at the secondary level. Students with disabilities often produce disorganized narratives with fewer narrative elements than their peers without disabilities. A multiple-probe design was used to examine effects of Self-Regulated Strategy Development for the P ick my genre then idea, O rganize my notes, W rite (POW) + S etting, T ension, rising A ction, C limax, S olution (STACS) strategy on narrative essay-writing skills for 6 secondary students with disabilities. Results indicated students improved the quality of their narratives and included a greater number of strategy-specific and story grammar elements following instruction. Students were also able to transfer skills across a history or social studies setting and could more accurately differentiate narrative writing prompts from expository and persuasive writing prompts. Treatment acceptability results indicated students found instruction beneficial.